1003. BIC/FTC/TAF Maintains Viral Suppression in Patients with Documented M184V/I Mutations: A Real World Experience. (31st December 2020) - Chamberlain, Nicholas; Brock, James B; Mena, Leandro A
Abstract: Background: The M184V/I mutation is a common mutation in treatment-experienced patients with HIV and confers high-level resistance to lamivudine and emtricitabine. Our objective is to assess the effectiveness of bictegravir (BIC)/emtricitabine (FTC)/tenofovir alafenamide (TAF) in a real-world setting in achieving and maintaining viral suppression in patients with documented M184V/I mutations. Methods: This case series is comprised of treatment-experienced HIV-positive patients with documented historical or newly-identified M184V/I mutations who were placed on BIC/FTC/TAF as a switch strategy or as therapy for patients who had failed a prior regimen. Patients with any resistance to tenofovir or bictegravir were excluded. Our primary outcome was sustained viral suppression at 12 months after initiation of BIC/FTC/TAF. Results: We included 33 patients (94% black, 52% male, median age 49, range 36-63) with an M184V/I mutation. The majority (91%) showed sustained viral suppression at 12 months of treatment. Non-adherence to medication was the common factor in all three cases of treatment failure. One patient developed an R263K mutation while on therapy, which conferred low-level resistance to bictegravir. There were no other instances of newly-acquired resistance to any of the components of BIC/FTC/TAF. Conclusion: Our results demonstrate high success rates of BIC/FTC/ATF in achieving and maintaining viral suppression in patients with documented M184V/I mutations who adhere to medications in a real-world setting with a single instance of new treatment-emergent resistance to bictegravir. These findings are congruent with reported sub-group analysis in clinical trial data and support the use of BIC/FTC/TAF in patients with M184V/I mutations. Disclosures: Leandro A. Mena, MD, MPH, Binx Health (Grant/Research Support)Evofem (Grant/Research Support)Gilead Science (Consultant, Grant/Research Support, Speaker's Bureau)GSK (Grant/Research Support)Janssen (Grant/Research Support)Merck (Consultant, Grant/Research Support)Roche Molecular (Consultant, Grant/Research Support)SpeedDx (Grant/Research Support)ViiV Healthcare (Consultant, Grant/Research Support, Speaker's Bureau)